Blue rubber bleb nevus syndrome associated with adult-onset cutaneous lesions and spontaneous intracranial hemorrhage: A case report and literature review - Chia-Hua Lin; Bai-Yao Wu; Chih-Tsung Hung; Hong-Wei Gao (Wolters Kluwer Medknow Publications, 2018)
Blue rubber bleb nevus syndrome (BRBNS) is a rare disorder. Since 1860, only 200 case reports of BRBNS have been reported. BRBNS is characterized by numerous malformations of the vascular system that significantly involve the skin, gastrointestinal tract, and other internal organs. We describe a 72-year-old Taiwanese man with BRBNS. Besides typical adult-onset cutaneous lesions, he had venous malformation in the central nervous system, which caused massive intracerebral hemorrhage. He has been in a stupor ever since. Physicians should recognize cutaneous BRBNS lesions early and be aware of the possible complications that arise from internal organs involved. Keywords: Bleeding, Central nervous system, Venous malformation, Blue rubber bleb syndrome, BRBNS